Chaguaceda et al. (2020) Oecologia dataset - Chaguaceda, Fernando; Eklöv, Peter; Scharnweber, Kristin (Uppsala University, 2020)
This dataset contains a series of variables over the ontogeny of a polymorphic perch (Perca fluviatilis) that live in pelagic and littoral habitats. The variables include: body size, growth, condition factor, C and N stable isotopes, diet estimations and % of different fatty acids in the dorsal muscle of perch. It also shows the isotope values of the food sources that were used as endpoints in the isotope mixing model. The dataset provides metadata of each variable.

The dataset was originally published in DiVA and moved to SND in 2024.

This dataset contains a series of variables over the ontogeny of a polymorphic perch (Perca fluviatilis) that live in pelagic and littoral habitats. The variables include: body size, growth, condition factor, C and N stable isotopes, diet estimations and % of different fatty acids in the dorsal muscle of perch. It also shows the isotope values of the food sources that were used as endpoints in the isotope mixing model. The dataset provides metadata of each variable.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Chaguaceda et al. (2020) Oecologia dataset
Keywords: Biology with specialization in Limnology; Biologi med inriktning mot limnologi; Ecology; Ekologi